2007
DOI: 10.1002/marc.200790000
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Rapid Commun. 1/2007

Abstract: Cover: Smectic-A Liquid Single Crystal Elastomers exhibiting optical transparency and spontaneous shape change are presented on the cover. Additionally, a simple model of the liquid crystalline phase is presented. The background shows a beautiful S A texture of the monomer taken between crossed polarizers. Further details can be found in the article by A. Komp, and H. Finkelmann* on page 55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…[9][10][11][12][13] There have been a few investigations on the reversible shape change of nematic elastomers; however, much less work has been carried out on that of smectic elastomers, in spite of their potentially useful mechanical properties, owing to their one-dimensional crystalline structure. [14][15][16][17][18][19][20][21][22] In 1997, Nishikawa et al [14] succeeded in preparing a smectic A single-crystal elastomer (SmA-LSCE) and reported that the elastic constant in the direction parallel to the layer normal was about two orders of magnitude larger than the elastic modulus in the direction parallel to the layer, becauseoftheone-dimensionalcrystalline structure and the two-dimensional liquid-like fluidity of the elastomer.…”
Section: Full Papermentioning
confidence: 99%
“…[9][10][11][12][13] There have been a few investigations on the reversible shape change of nematic elastomers; however, much less work has been carried out on that of smectic elastomers, in spite of their potentially useful mechanical properties, owing to their one-dimensional crystalline structure. [14][15][16][17][18][19][20][21][22] In 1997, Nishikawa et al [14] succeeded in preparing a smectic A single-crystal elastomer (SmA-LSCE) and reported that the elastic constant in the direction parallel to the layer normal was about two orders of magnitude larger than the elastic modulus in the direction parallel to the layer, becauseoftheone-dimensionalcrystalline structure and the two-dimensional liquid-like fluidity of the elastomer.…”
Section: Full Papermentioning
confidence: 99%
“…In smectic-A-elastomers, where the smectic layers are oriented perpendicular to the director, orientation of the director also results in a macroscopic orientation of the smectic layers. [18][19][20][21] In the case of the SmC-phase, both chiral and achiral, a uniaxial field is not sufficient anymore to obtain a liquid single crystal elastomer. In these liquid crystals, the smectic layer normal is not oriented parallel to the director but tilted by the angle θ.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Komp and Finkelmann [8] and Stannarius et al [9] investigated S A -LSCEs which clearly differed from Nishikawa's system in their response to mechanical stress. Komp and Finkelmann used the same backbone, crosslinker and preparation technique but incorporated a side-on mesogen carrying fluorinated tails.…”
Section: Introductionmentioning
confidence: 99%